An Enhancement of AODV routing protocol for more robust wireless sensor network - Che-Aron, Zamree; Al-Khateeb, Wajdi Fawzi Mohammed; Anwar, Farhat (IJCNS, 2010)
As more and more real Wireless Sensor Network’s (WSN) applications have been tested and deployed over the last decade, the research community of WSN realizes that several issues need to be revisited from practical angles, such as reliability and availability. Furthermore, fault-tolerance is one of the main issues in WSNs since it becomes critical in real deployed environments where network stability and reduced inaccessibility times are important. Basically, wireless sensor networks suffer from resource limitations, high failure rates and faults caused by the defective nature of wireless communication and the wireless sensor itself. This can lead to situations, where nodes are often interrupted during data transmission and blind spots occur in the network by isolating some of the devices. In this paper, we address the reliability issue by designing an enhanced fault-tolerant mechanism for Ad hoc On-Demand Distance Vector (AODV) routing protocol used in WSN called the ENhancement of FAult-Tolerant AODV (ENFAT-AODV) routing protocol. We design and implement the backup route scheme by creating a backup path for all nodes along a main path of data delivery in the network. When a node gets failure to deliver the data packet through the main route, it immediately employs its backup route to become its new main path instead of the previously broken one to reduce a number of data packets dropped because of route break and to maintain the continuity of data packet delivery in presence of some faults (nodes failure and links error). Moreover, this proposed routing protocol also satisfies the low transmission delay and gets better throughput results. Consequently, the reliability, availability and maintainability of the network are achieved. The simulation shows that our proposed routing scheme is better than the original AODV routing.